Monitoring Detak Jantung untuk Atlet Lari 100 Meter Berbasis Internet of Things - Hidayat, Muhammad Aksa; Sukaridhoto, Sritrusta; Basuki, Achmad; Falah, Muhammad Fajrul (INTEK: Jurnal Penelitian, 2019)
Abstract— At the 2018 ASEAN Games, Indonesia won 98 medals, the number of medals exceeded the expected target, this achievement could not be separated from the role of coaches who always monitor the condition of their athletes while training on the field. One of the conditions of monitoring athletes can be done by monitoring the heartbeat activity of each athlete during exercise. In this study the authors made a heart rate monitoring tool for IoT 100 meter runners that can be used in the field and send data in real time. Polar Heart Rate heart rate sensor is good to use because the data reading error is 0.4%. 2. heart rate monitoring can only communicate up to 70 meters more. Data entered and read well into the server.